Burn - Banks, Maya (New York : Berkley Books, 2013)
When it comes to sex, Ash McIntyre has always explored his wilder side. Extreme and uncompromising, he demands control. And he prefers women who want it like that. Then Ash meets Josie, who seems immune to his charms and his wealth. Intrigued, he begins a relentless pursuit, determined she won't be the one who got away. He never imagined the one woman to tell him no would be the only woman who'd ever drive him to the edge of desire...
PUBLISHER'S NOTE: "The recipes contained in this book are to be followed exactly as written."
"Mature audience."
Keywords: Bondage (Sexual behavior) -- Fiction; Man-woman relationships -- Fiction; Sexual dominance and submission -- Fiction; Erotic fiction